Development of a Flipped Classroom Learning Model Using the Discord Application to Improve the Student Learning Effectiveness of Class XII of Zion Senior High School, Makassar - Padaunan, Auditio; Djadir, Djadir; Bernard, Bernard (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
This research is a development research or Research and Development (R&D). The product development process refers to the ADDIE model. The research was conducted at SMA Zion Makassar in the even semester of the 2024/2025 academic year. The operational test of the product was carried out in class XII Thames, which consisted of 34 students. The data analysis techniques used were descriptive and inferential statistical analysis on validity, practicality, and effectiveness. The research results showed: (1) the results of the lesson plan product assessment and other instruments from 2 validators were obtained at 0.83 in the valid category; (2) the results of practicality were assessed from the implementation and teacher responses obtained 93.5% in the very practical category; (3) the effectiveness of the product was assessed based on the aspect of student activity observation obtained 97% with a very high category, the aspect of student response obtained 89% in the very high category, the aspect of classical completeness obtained 88% in the high category, the aspect of normalized N-Gain obtained 0.78 very high, and the aspect of the average posttest results obtained 89.53, all aspects met the effective requirements. In addition, normality, homogeneity, and paired sample t-test tests were carried out. The results obtained data were normally distributed and homogeneous because the significance value was >0.05, and there were differences in learning outcomes because the significance value was 0.00 <0.05. Based on this, the product is valid, practical, and effective in improving student learning outcomes.